Programmed Elections: The Impact of Artificial Intelligence on the Electoral Process - Lopes, Alexandre Rosa (Law, State and Telecommunications Review, 2025)
[Purpose] This study analyzes the impact of Generative Artificial Intelligence (AI) on the integrity of the electoral process. [Methodology/approach/design] It employs a multidisciplinary approach that integrates Law, Behavioral Economics, and Nonviolent Communication (NVC) to investigate how AI amplifies electoral manipulation by exploiting voter cognitive biases. [Findings] The paper assesses the risks of regulation, such as censorship and political instrumentalization, and concludes that the technology represents a rupture with historical manipulation tactics due to its scale and precision. [Practical implications] The findings suggest the solution transcends the mere prohibition of AI use and development, and should instead focus on voter empowerment through transparency and education. [Originality/value] Finally, the paper's originality lies in its adoption of Behavioral Economics as an analytical framework for AI's influence and in the innovative application of NVC to develop informational filters that assist communication, thereby strengthening voter autonomy.